Méthodes adaptatives pour les problèmes d’endommagement - Jay, Guillaume; Aubry, Denis; Tié, Bing; Muzzolini, Raphaël (European Journal of Computational Mechanics, 2002)
This paper presents the use of adaptive methods for damage problems with the Gurson model. Both mesh and model (3D / shell) adaptivities are considered. Mesh adaption is done by remeshing the structure with discretization error indicators based on the residual method. For model adaptivity, investigation of the model error highlights the inconsistency of plane strain Mindlin kinematics with the associated plane stress constitutive law. Two solutions are suggested herein to overcome this inconsistency in error estimation. Error indicators are then suggested. Several numerical examples are presented to emphasize the efficiency of the approach and advantages of mesh and model adaptivities to describe properly damage phenomena.